Unreliable narrator as a textual and interpretative problem - Pechal, Zdenek (Bohemica Olomucensia, 2013)
The unreliable narrator is a part of the fictional world and his complex of mediation. The unreliable narrator is based on the contradiction which can be identified inside of the fictional world. The perceiver does not create the contradiction of the unreliable narrator but he reacts on his determinateness. We identify the contradiction of the unreliable narrator as the contradiction between the story and plot, between the narrator and the reflector, between different existential areas of the fictional world and between the internal and external perspective of the fictional world. We proved these contradictions on the texts from the Russian literature. It seems to us that the way how to express the situation of the unreliable narrator is by using a metaphor - an example from the text by Nabokov (1991, s. 248):"We all admire the spangled acrobat with classical grace meticulously walking his tight rope in the talcum light; but how much rarer art there is in the sagging rope expert wearing scarecrow clothes and impersonating a grotesque drunk! I should know."